Performance of an algorithm‐based approach to the diagnosis and management of functional gastrointestinal disorders: A pilot trial. Issue 1 (2nd November 2017) - Linedale, E. C.; Mikocka‐Walus, A.; Vincent, A. D.; Gibson, P. R.; Andrews, J. M.
Abstract: Background: Recent advances in the development of diagnostic criteria and effective management options for functional gastrointestinal disorders (FGIDs) have not yet been integrated into clinical practice. There is a clear need for the development and validation of a simple clinical pathway for the diagnosis and management of FGIDs which can be used in primary care. Methods: In this controlled pilot study, we designed and evaluated a non‐specialist‐dependent, algorithm‐based approach for the diagnosis and management of FGIDs (ADAM‐FGID). Patients referred to 1 tertiary referral center with clinically suspected functional gastrointestinal disorders were allocated to waitlist control or algorithm group. The algorithm group was screened for organic disease, and those without clinical alarms received a written FGID diagnosis and management options. All participants were followed up for 1 year. Key Results: The ADAM‐FGID was found to be feasible and acceptable to both patients and primary healthcare providers. The diagnostic component identified that 39% of referrals required more urgent gastroenterological review than original triage category, with organic disease subsequently diagnosed in 31% of these. The majority of patients (82%) diagnosed with a FGID did not receive a relevant alternative diagnosis during follow‐up. Patient buy‐in to the model was good, with all reading the diagnostic/management letter, 80% entering management, and 61% reporting symptom improvement at 6 weeks. Moreover, 68% of patients and all referring doctors found the approach to be at least moderately acceptable. Patients reported being reassured by the approach and found the management options useful. Primary healthcare providers acknowledged the potential of this approach to reduce waiting times for endoscopic procedures and to provide reassurance to both patients and themselves. Conclusions & Inferences: This pilot study provides preliminary evidence to support a clinical pathway for the diagnosis and management of FGIDs which does not depend upon specialist review. Further rigorous testing within primary care is needed to conclusively establish safety and efficacy. However, this approach is safer than current management and has potential to build capacity by reducing specialist burden and expediting effective care. Abstract : In this controlled study, we designed and piloted a non‐specialist‐dependent, algorithm‐based approach for the diagnosis and management of FGIDs (ADAM‐FGID). The ADAM‐FGID was found to be feasible and acceptable to both patients and primary healthcare providers. This approach is safer than current management assisting in the earlier detection, diagnosis, and treatment of organic disease and has potential to build capacity by reducing specialist burden and expediting effective care.